Friars and their influence in Medieval Spain (Church, faith, and culture in the Medieval West., 2018)
This book explores how the Spanish kingdoms were highly influenced by the arrival of the Dominican and Franciscan friars in the thirteenth century. The Dominicans and the Franciscans, who were already very active in the Peninsula in the life of their founder, Francis of Assisi, were particularly prominent. The Dominican and Franciscan friars were to have an enormous impact, pervading almost every aspect of the society of late medieval Spain. In a revolutionary break from the Church's past these religious were heavily involved in the world, in preaching the message of the Gospel to the laity, while in education, they produced many of the greatest scholars of the age. Likewise, they transformed urban life, becoming an essential part of the fabric of the late medieval city. Equally the friars transformed the hierarchy of the Church, often taking up major positions in the episcopate. The friars were to the fore in the establishment of the Inquisition in the Crown of Aragon and, for very similar reasons, played the major part in attempting to teach the Gospel message to the Muslims as the Christian kingdoms expanded to the south. They greatly influenced the policies of monarchs such as that of James I of Aragon and Ferdinand III of Castile. Their missions in the towns and their educational role, as well as their strong associations with the papacy and the crown, often lead them into conflict with other religious and with secular society. They also suffered internal tensions and major splits. They were to be both widely admired and the subject of biting literary satire. Francisco García-Serrano ultimately argues how the story of medieval Spain cannot possibly be told without these important groups of friars.